Meningkatkan Hasil Belajar Siswa SD Negeri 03 Sebungkang Melalui Model Problem Based Learning (PBL) Berbantuan PPT pada Pendidikan Agama Katolik - Sabina Kuni Bulu; Hartutik Hartutik; Sugiyana Sugiyana (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This research aims to describe the application of the Problem Based Learning (PBL) model with the help of PPT in learning Catholic Religious Education and Character at SD Negeri 03 Sebungkang, analyze the increase in student learning outcomes after implementing the Problem Based Learning (PBL) model with the help of PPT in the subjects of Catholic Religious Education and Character and also determine the influence of the Problem Based Learning (PBL) model with the help of PPT on students' motivation and active participation in the learning process. The research method used is classroom action research (CAR), with a focus on improving student learning outcomes and active participation. Classroom action research was conducted in two cycles and involved grade III students. By conducting this research, it is expected to improve student learning outcomes, both in academic understanding, motivation, and active participation of students. In this study, 24 grade III students were involved, and data were collected through observation, tests, and interviews. The results of the study showed that the application of the PBL model with the help of PPT succeeded in improving student learning outcomes. In cycle I, the average post-test score reached 71, while in cycle II, the average score increased to 83. The application of this model also encourages students to be more active in group discussions, thus increasing their motivation and participation in learning. Observation of student activities shows that they are more enthusiastic and involved in the problem-solving process presented. This study contributes to the development of learning methods in the field of Catholic Religious Education, and can be a reference for other teachers in implementing innovative learning models. The results of this study can encourage the application of the PBL method more widely, thereby improving the quality of learning and the achievement of Basic Competencies (KD) in schools. Thus, the application of the PPT-assisted PBL model has proven effective in improving learning outcomes and active participation of students in religious education.